The physical and motor development of 9-year-old children attending football classes in "football school for children" - Klimczyk, M.; Stec, M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: The purpose of the study was to determine the physical development and physical fitness of the boys at the age of 9 years old attending football classes.